2012
DOI: 10.1098/rstb.2012.0229
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the light-harvesting chlorophyll antenna size in Chlamydomonas reinhardtii by TLA1 gene over-expression and RNA interference

Abstract: Truncated light-harvesting antenna 1 (TLA1) is a nuclear gene proposed to regulate the chlorophyll (Chl) antenna size in Chlamydomonas reinhardtii. The Chl antenna size of the photosystems and the chloroplast ultrastructure were manipulated upon TLA1 gene over-expression and RNAi downregulation. The TLA1 over-expressing lines possessed a larger chlorophyll antenna size for both photosystems and contained greater levels of Chl b per cell relative to the wild type. Conversely, TLA1 RNAi transformants had a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 70 publications
1
27
0
Order By: Relevance
“…This statement is supported by the following. The Chl a : b ratio in C. ohadii is naturally high, twice that found in C. sorokiniana and three‐ to four‐fold higher than that in other green algae such as C. vulgaris (Kowallik & SchĂŒrmann, ) and C. reinhardtii, and similar to that observed in the TLA1 mutant thereof (Mitra et al ., ). Chl b is associated with the light‐harvesting complexes; its low abundance in C. ohadii suggests a relatively small functional light‐harvesting cross‐section, which, unlike C. sorokiniana , did not change after exposure to high illumination (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…This statement is supported by the following. The Chl a : b ratio in C. ohadii is naturally high, twice that found in C. sorokiniana and three‐ to four‐fold higher than that in other green algae such as C. vulgaris (Kowallik & SchĂŒrmann, ) and C. reinhardtii, and similar to that observed in the TLA1 mutant thereof (Mitra et al ., ). Chl b is associated with the light‐harvesting complexes; its low abundance in C. ohadii suggests a relatively small functional light‐harvesting cross‐section, which, unlike C. sorokiniana , did not change after exposure to high illumination (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…A study with the truncated light‐harvesting antenna 1 (TLA1) gene, which is proposed to regulate the chlorophyll (Chl) antenna size in C. reinhardtii , showed that overexpressing and RNAi silencing modulate the expression of light‐harvesting protein, which provides a mechanistic understanding of the Chl antenna size regulation by this gene (Mitra et al . ). Moreover, inducing RNAi‐mediated silencing of the chlorophyllide an oxygenase (CAO) gene, chlorophyll b levels were partially reduced.…”
Section: Rna Interferencementioning
confidence: 97%
“…In the model green alga C. reinhardtii, notable advances have enabled starch hyperaccumulation [87,103], reduction of light-harvesting antennae for more efficient light harvesting [104][105][106][107], and increased TAG accumulation in starchless mutants [86,87,[108][109][110]]. In the model diatom Phaeodactylum tricornutum, medium chain fatty acid synthesis and incorporation into TAG has been accomplished [83].…”
Section: Intracellular Triacylglycerol and Starch Accumulationmentioning
confidence: 99%